The EB-MB Transition at Tell Afis: a Reappraisal - Candida Felli (Asia Anteriore Antica)
The passage from the 3rd to the 2nd millennium BC in Inner Syria is still a matter for debate both in historical and archaeological studies. This is only partially due to lack of evidence: it is much the way one interprets the extant evidence that affects the discourse, emphasizing a break or a transition, and viewing this time as a period of crisis or not. In this article relevant archaeological evidence from the site of Tell Afis is revised and some new data, including 14C dates, are offered in order to resume discussion on the question. Focus will be specifically on pottery: by recovering various strands of development in the local pottery repertoires from the Early Bronze to the Middle Bronze, the article aims to contribute to the reconstruction of this archaeological phase at a regional level as well.